Rich digital collaborations in a small rural community - Dix, Alan; Malizia, Alessio; Turchi, Tommaso; Gill, Steve; Louden, Garreth; Morris, Richard; Chamberlain, Alan; Belluci, Andrea (Springer, 2017)
In this chapter we describe experience in the design and installation of a low-cost multi-touch table in a rural island community. We will discuss the creation of the table including: pragmatic challenges of installation, and then re-installation as the physical fabric of the multi-purpose building (café, cinema, meeting area and cattle market) altered; technical challenges of using off-the-shelf components to create state-of-the art multi-touch interactions and tactile BYOD (bring your own device) end-user programming; design challenges of creating high-production value bespoke mountings and furniture using digital fabrication in an environment that could include sewing needles, ketchup laden sandwiches and cow manure. The resulting installation has been used in semi-in-the-wild studies of bespoke applications, leading to understandings of the way small communities could use advanced interactions. More broadly this sits within a context of related studies of information technology in rural developments and a desire to understand how communities can become users of the rich streams of open data now available, and, perhaps more important, offer ways in which small communities can become empowered through the creation and control of their own data.